Natural gas distribution proposal in Lima's urban hills through lean logistic and mixed whole linear programming. (February 2020) - Balvin, Luis; Gomez, Sandra; León, Claudia; Alvarez, José C.
Abstract: The availability of natural gas in Lima — Peru, from Camisea, in several urban areas of Lima, for technical reasons there are no natural gas facilities especially in peripheral urban areas in the highlands or hills. This is compensated by FISE government social programs providing subsidized liquefied petroleum gas balls. In this context, a proposal has been developed to provide natural gas to these elevated areas, in particular to Cerro San Cristóbal, located in the boundaries of the districts of Rímac and San Juan de Lurigancho — Lima. This proposal is based on the principles of Lean Logistic and linear programming of mixed burials. The results will imply a better supply of natural gas to peripheral areas and energy poverty, the inherent security problems must also be addressed.